Leg bones of a new penguin species from the Waipara Greensand add to the diversity of very large-sized Sphenisciformes in the Paleocene of New Zealand. Issue 1 (2nd January 2020) - Mayr, Gerald; De Pietri, Vanesa L.; Love, Leigh; Mannering, Al; Scofield, R. Paul
Abstract : Mayr, G., De Pietri, V.L., Love, L., Mannering, A. & Scofield, R.P., 9 August 2019. Leg bones of a new penguin species from the Waipara Greensand add to the diversity of very large-sized Sphenisciformes in the Paleocene of New Zealand. Alcheringa 44, 194–201. ISSN 0311-5518 We describe a new large-sized species of the Sphenisciformes (penguins) from Paleocene strata of the Waipara Greensand in New Zealand. ? Crossvallia waiparensis, sp. nov. is represented by leg bones of a single individual as well as two tentatively referred proximal humeri and resembles Crossvallia unienwillia from the late Paleocene of Antarctica in size and morphology. The new species is the fifth published species of stem group Sphenisciformes from the Waipara Greensand and the fourth one, which has been formally named. It is distinguished from a recently reported tarsometatarsus of an unnamed large-sized penguin species from the Waipara Greensand and is the oldest well-represented giant penguin. ? C. waiparensis approaches the size of the Eocene taxa Anthropornis and Palaeeudyptes and provides further evidence that penguins attained a very large size early in their evolutionary history. Gerald Mayr [gerald.mayr@senckenberg.de ], Senckenberg Research Institute and Natural History Museum Frankfurt, Ornithological Section, Senckenberganlage 25, D-60325 Frankfurt am Main, Germany; Vanesa L. De Pietri [vdepietri@canterburymuseum.com ], Al Mannering [alman@slingshot.co.nz ], R. Paul Scofield [pscofield@canterburymuseum.com ], Canterbury Museum, Rolleston Avenue, Christchurch 8050, New Zealand; Leigh Love [lvlove@xtra.co.nz ], PO Box 49, Waipara 7483, New Zealand.